New species of insect trypanosomatids from Costa Rica and the proposal for a new subfamily within the Trypanosomatidae - Jirků, Milan; Yurchenko, Vyacheslav Y; Lukeš, Julius; Maslov, Dmitri A (The Journal of eukaryotic microbiology, 2012)
Several new species of trypanosomatids (Euglenozoa, Kinetoplastea, Trypanosomatidae), isolated from the intestines of Neotropical insects (Heteroptera), were genotyped on the basis of spliced leader RNA, and also defined phylogenetically using gene sequences of small subunit ribosomal RNA and glycosomal glyceraldehyde phosphate dehydrogenase. The taxonomic descriptions also included characterization using morphometry and electron microscopy. Our phylogenetic analyses placed the new species within the clade, previously designated "SE" for "Slowly Evolving" sequences of ribosomal RNA genes, a clade that also includes numerous monoxenous parasites of insects from the genera Crithidia, Leptomonas, and Wallaceina, as well as the dixenous genus Leishmania. Based on the high phylogenetic support for this clade, which is consistently recovered in all recent phylogenetic reconstructions, a proposal is put forward to recognize this natural taxon as a new subfamily, Leishmaniinae, within the family Trypanosomatidae.
Keywords: RNA ribozomální 18S; Microscopy; geny rRNA; protozoální DNA; Insecta; Genes, rRNA; RNA protozoální; Animals; mikroskopie; molekulární sekvence - údaje; ribozomální DNA; shluková analýza; Cluster Analysis; DNA, Protozoan; RNA, Protozoan; Molecular Sequence Data; Trypanosomatina; hmyz; Glyceraldehyde-3-Phosphate Dehydrogenase (Phosphorylating); glyceraldehyd-3-fosfátdehydrogenasa (fosforylační); Sequence Analysis, DNA; Kostarika; zvířata; fylogeneze; sekvenční analýza DNA; DNA, Ribosomal; Costa Rica; Phylogeny; RNA, Ribosomal, 18S